Single pyrimidine discrimination during voltage-driven translocation of osmylated oligodeoxynucleotides via the α-hemolysin nanopore - Ding, Yun; Kanavarioti, Anastassia (Beilstein Journal of Nanotechnology, 2016)
The influence of an electric field on an isolated channel or nanopore separating two compartments filled with electrolytes produces a constant ion flux through the pore. Nucleic acids added to one compartment traverse the pore, and modulate the current in a sequence-dependent manner. While translocation is faster than detection, the α-hemolysin nanopore (α-HL) successfully senses base modifications in ssDNA immobilized within the pore. With the assistance of a processing enzyme to slow down translocation, nanopore-based DNA sequencing is now a commercially available platform. However, accurate base calling is challenging because α-HL senses a sequence, and not a single nucleotide. Osmylated DNA was recently proposed as a surrogate for nanopore-based sequencing. Osmylation is the addition of osmium tetroxide 2,2’-bipyridine (OsBp) to the C5–C6 pyrimidine double bond. The process is simple, selective for deoxythymidine (dT) over deoxycytidine (dC), unreactive towards the purines, practically 100% effective, and strikingly independent of length, sequence, and composition. Translocation of an oligodeoxynucleotide (oligo) dA10XdA9 via α-HL is relatively slow, and exhibits distinct duration as well as distinct residual current when X = dA, dT(OsBp), or dC(OsBp). The data indicate that the α-HL constriction zone/β-barrel interacts strongly with both OsBp and the base. A 23 nucleotide long oligo with four dT(OsBp) traverses 18-times slower, and the same oligo with nine (dT+dC)(OsBp) moieties traverses 84-times slower compared to dA20, suggesting an average rate of 40 or 180 μs/base, respectively. These translocation speeds are well above detection limits, may be further optimized, and clear the way for nanopore-based sequencing using osmylated DNA.
Keywords: DNA sequencing; α-hemolysin; ion-channel measurements; nanopore; osmium tetroxide bipyridine; osmylated oligos; osmylation; single-stranded DNA (ssDNA)